Assessment of the stakeholders understanding of a sustainable community and the sustainability of their initiative : a case of Tsilitwa Project in the Mhlontlo Local Municipality, Eastern Cape - Olwoch, Jane Mukarugwiza (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2013.